Integrated Isogenic Human Induced Pluripotent Stem Cell–Based Liver and Heart Microphysiological Systems Predict Unsafe Drug–Drug Interaction - Lee-Montiel, Felipe T.; Laemmle, Alexander; Charwat, Verena; Dumont, Laure; Lee, Caleb S.; Huebsch, Nathaniel; Okochi, Hideaki; Hancock, Matthew J.; Siemons, Brian; Boggess, Steven C.; Goswami, Ishan; Miller, Evan W.; et al. (Frontiers in Pharmacology, 2021)
Three-dimensional (3D) microphysiological systems (MPSs) mimicking human organ function in vitro are an emerging alternative to conventional monolayer cell culture and animal models for drug development. Human induced pluripotent stem cells (hiPSCs) have the potential to capture the diversity of human genetics and provide an unlimited supply of cells. Combining hiPSCs with microfluidics technology in MPSs offers new perspectives for drug development. Here, the integration of a newly developed liver MPS with a cardiac MPS—both created with the same hiPSC line—to study drug-drug interaction (DDI) is reported. As a prominent example of clinically relevant DDI, the interaction of the arrhythmogenic gastroprokinetic cisapride with the fungicide ketoconazole was investigated. As seen in patients, metabolic conversion of cisapride to non-arrhythmogenic norcisapride in the liver MPS by the cytochrome P450 enzyme CYP3A4 was inhibited by ketoconazole, leading to arrhythmia in the cardiac MPS. These results establish functional integration of isogenic hiPSC-based liver and cardiac MPSs, which allows screening for DDI, and thus drug efficacy and toxicity, in the same genetic background.